Bioplastics: A new analytical challenge - Censi, Valentina; Saiano, Filippo; Bongiorno, David; Indelicato, Serena; Napoli, Anna; Piazzese, Daniela (Frontiers in Chemistry, 2022)
Even though petroleum-based plastics are advantageous in complying with the performance requirements in many applications, these are related, throughout their life cycle, to several environmental problems, including greenhouse gas emissions and persistence in marine and terrestrial environments. Therefore, the preservation of natural resources and climate change is considered worldwide, the main reason for which is necessary to reduce consumption and dependence on fossil-based materials. Biopolymers (PLA, PHB, PHA, etc.) are examples of plastics whose use is grown exponentially over the years because of, in particular, the improvements of their physical and mechanical properties using additives of various nature and depending on the scope of application. This review aims to discuss various ways of biopolymer degradation, to evaluate if they represent a new frontier in eco-sustainability or rather a re-proposal of old problems. Related to this topic, we also have focussed our attention on the different methods for the quantitative analysis of bioplastics, or their degradation by-products, comparing and evaluating the advantages and disadvantages of each technique.